METHODOLOGICAL STRATEGIES FOCUSED ON TEACHING CHILDREN WITH ATTENTION DEFICIT DISORDER WITH HYPERACTIVITY AT SCHOOL META – MACAPÁ/AP - Roberta de Souza Marinho, Cleuma; Da Silva Amaral, Jhuliana; Santos Dos Santos, Joyce; Adnilton Oliveira Ferreira, José (Revista Gênero e Interdisciplinaridade, 2023)
In this present work, the main objective is to investigate the methodological strategies and resources used in the pedagogical practice for the learning and teaching of children with ADHD, identifying the main difficulties in the pedagogical practices in the learning process of these children and finally to analyze the contributions of teaching practice, as a facilitator of learning. In this context, the research was carried out based on the following problem question: What methodological strategies and resources are used in the pedagogical practice for teaching and learning children with ADHD? The study presented significant theoretical and practical contributions to the aforementioned process. The problem and the objectives proposed for the research led us to develop a field research that is guided by a qualitative approach. Among the types of qualitative research, we opted for the Case Study, understanding that it meets the objectives defined in this study, which aim to know how, in fact, the methodological strategies and resources used in the pedagogical practice for the learning and teaching of children with ADHD. Qualitative research provides direct contact between the researcher and the researched environment. This type of Study, when defined, is characterized as a Case Study. In this case, the study included the teacher who has a child diagnosed with ADHD in her classroom and the pedagogical coordinator of the researched school. In the results it was possible to perceive that the teacher knows about the disorder and has her own means of dealing with children with ADHD in the classroom, so we will show studies that can contribute to the aid of these pedagogical practices being more directed to the specificities of these children, aiming at a better learning. The study presented significant theoretical and practical contributions to the aforementioned process. The theoretical contributions refer to the new discoveries that were made from the investigation of the teacher’s pedagogical practice and the physical and pedagogical structure of the school to serve students with ADHD.